The University of Cambridge in the Age of Atlantic Slavery - Bell-Romero, Nicolas (Cambridge University Press, 2026)
In this first history of the University of Cambridge's involvement in slavery and abolition, Nicolas Bell-Romero uncovers the extent to which the problem of slavery was an inextricable feature of social, economic, cultural, and intellectual life throughout Britain. This title is also available as open access on Cambridge Core.